Variation of the Amount of Seeds per Planting Hole to the Response of Lettuce Plant with DFT Hydroponic System - Akhmad Zaki; Akhmad Gazali; Nukhak Nufita Sari (Universitas Sembilanbelas November Kolaka, 2022)
Lettuce is a vegetable plant whose needs always increase every year according to population growth. Therefore, it is necessary to make efforts to increase the production of lettuce by increasing the number of seeds per planting hole using the DFT hydroponic system. This study aims to determine the effect of the number of seeds per planting hole on the growth and yield of lettuce plants and to determine the number of seeds per planting hole that produces the highest growth and yield of lettuce plants. Implementation This research was conducted from August to September 2021. Located in the Community Food Barn, the Department of Food Security and Fisheries, Banjar Regency. The method used in this study was a completely randomized design (CRD) with treatment S1 (control), S2 (2 seeds per planting hole), S3 (3 seeds per planting hole), and S4 (4 seeds per planting hole). The treatment was repeated 4 times to get 16 experimental unit Based on the results of the research, it can be seen that the number of seeds per planting hole has an effect on the growth and yield of lettuce. The best treatment was found in S4 which had the highest value at an average plant height of 36.25 cm, an increase in plant height at 28 DAP of 11.61 cm, an average number of leaves of 22.06 strands, and an average yield harvest of 153.75 grams. DFT hydroponic cultivation of lettuce resulted in optimal production of 4 seeds per planting hole. Useful research for the efficiency of lettuce production using hydroponics. In addition to production efficiency, it is necessary to consider plant competition to utilize existing resources for optimal growth